Effectiveness of Syphilis Partner Notification After Adjusting for Treatment Dates, 7 Jurisdictions. Issue 2 (February 2022) - Cope, Anna Barry; Bernstein, Kyle T.; Matthias, James; Rahman, Mohammad; Diesel, Jill C.; Pugsley, River A.; Schillinger, Julia A.; Chew Ng, Rilene A.; Klingler, Ellen J.; Mobley, Victoria L.; Samoff, Erika; Peterman, Thomas A.
Abstract : Background: Disease intervention specialists (DIS) prevent syphilis by ensuring treatment for patients' sex partners through partner notification (PN). Different interpretations of how to measure partners treated due to DIS efforts complicates PN evaluation. We measured PN impact by counting partners treated for syphilis after DIS interviewed the patient. Methods: We reviewed data from early syphilis cases reported during the 2015–2017 period in 7 jurisdictions. We compared infected partners brought to treatment using the following: (1) DIS-assigned disposition codes or (2) all infected partners treated 0 to 90 days after the patient's interview (adjusted treatment estimate). Stratified analyses assessed patient characteristics associated with the adjusted treatment estimate. Results: Disease intervention specialists interviewed 23, 613 patients who reported 20, 890 partners with locating information. Many of the 3569 (17.1%) partners classified by DIS as brought to treatment were treated before the patient was interviewed. There were 2359 (11.3%) partners treated 0 to 90 days after the patient's interview. Treatment estimates were more consistent between programs when measured using our adjusted estimates (range, 6.1%–14.8% per patient interviewed) compared with DIS-assigned disposition (range, 6.1%–28.3%). Treatment for ≥1 partner occurred after 9.0% of interviews and was more likely if the patient was a woman (17.9%), younger than 25 years (12.6%), interviewed ⩽7 days from diagnosis (13.9%), HIV negative (12.6%), or had no reported history of syphilis (9.8%). Conclusions: Counting infected partners treated 0 to 90 days after interview reduced variability in reporting and facilitates quality assurance. Identifying programs and DIS who are particularly good at finding and treating partners could improve program impact. Abstract : Counting infected partners treated 0 to 90 days after the patient's interview as opposed to using disposition code assignments reduced variability in reporting across jurisdiction and can facilitate quality assurance.